The choice of instrument for EU legislation: mapping the system of governance under MiFID II and MiFIR (2020)
Centralisation is a coat of many colours, and as is shown in this book it can be studied from many perspectives. Perhaps the broadest stripes in the pattern are those of the legal instruments governing the field at issue – in this case financial markets in the EU. This study focuses particularly on governance of EU markets in financial instruments under Directive 2014/65/EU of the European Parliament and of the Council of 15 May 2014 on markets in financial instruments [MiFID II], and Regulation (EU) No 600/2014 of the European Parliament and of the Council of 15 May 2014 on markets in financial instruments [MiFIR].